ANDROID-BASED HEALTH POST MANAGEMENT APPLICATION DESIGN CLINICS IN INDONESIA - Dwi Kartinah (Asosiasi Dosen Muda Indonesia, 2023)
This research aims to design and develop an Android-based application that can help manage Pos Sehat, especially in rural areas of Indonesia, in order to increase the efficiency and effectiveness of health services. The focus of this research is developing applications for Pos Sehat managers, with important features such as patient monitoring, viewing patient biodata, tracking disease history, and drug recommendations. The research method involves planning research, studying literature, developing applications using Android Kotlin for UI/UX, Node.js for backends, and cloud services or Firebase for data storage, as well as application testing and evaluation. The results of the study show that the application developed can increase the efficiency and effectiveness of the management of the Health Post, facilitate access to patient and drug information, and assist in the decision-making process regarding the management of the Health Post. This research is expected to be a reference for similar research and inspire further development in the field of technology-based health management.